COMICS IN THE CLASSES OF PHYSICAL EDUCATION: A CRITICAL-SURPASSING APPROACH (Fiep Bulletin - online, 2011)
This paper aims to clarify possible contributions of the use of comic books to the teaching of physical education in the school. The comics can be an important tool for studying the content of that discipline by providing an enjoyable and stimulating reading, which facilitates assimilation by the students, whenever the texts involve more complex analysis of the elements of corporal culture. On a critical-surpassing approach, in addition to the experiences of the elements of corporal culture, it is necessary to study the relationships of these with the wider social practice, which can be done from reading comics as these factors are present. The example given here is a story of Turma da Mônica, from which the historical aspects of the Olympic Games can be discussed with the students. After the arguments presented here, is possible to conclude that the comics are an important teaching tool in the introduction of more complex studies involving components of corporal culture.
Keywords: Physical Education class; Comics in education; Education - Philosophy